An Investigation Of Fracture Toughness On Heat Treated Aluminum Alloy 7075 With Effect Of Corrosion - Siti Khadhijah , Mohamad (UTeM, 2010)
The aim of this project is to investigate the fracture toughness of heat treated Aluminum Alloy 7075 (AA7075) with effect of corrosion. As we know, characteristics of Aluminum are soft, light weight, and high corrosion resistant, but low strength. In this research, AA7075 is used as raw material. This AA7075 will be heated to T6, T73, and retrogression and re-aging (RRA) at proper temperature. After heat treatment, several specimens will be corroded by doing immersion in chemical solution corrosion process. But the important thing is we need to record the reading of hardness of each specimen before and after corrosion process. Finally, the specimen will be test by doing fracture toughness test, hardness test, and microstructure observation. The new properties of AA7075 are developing by heat treatment. We can compare the hardness, microstructure of phases and fracture surface and then decide which process is better to improve and build an excellent properties for future application.